Analisis Kebangkrutan Dengan Metode Altman Z-Score Dan Zmijewski Pada PT. BATA Periode tahun 2019-2023 - Eka sufiriyani (CV. ITTC INDONESIA, 2024)
In predicting bankruptcy, there are several types of methods that can be used and it is possible that each calculation result of the method to predict bankruptcy will be the same or even different because each method has its own characteristics. This study aims to compare the Altman Z-Score and Zmijewski X-Score bankruptcy prediction methods for PT BATA Tbk for the 2019-2023 period. This type of research is descriptive quantitative, the population in this study is the financial statements of PT BATA Tbk. The sample in this study is in the form of financial statements in 2019-2023. Based on the results of the Altman Z-Score analysis, the calculation results in 2019 amounted to 2.82 which is in the Gray Area condition. In 2020 the Z-Score value of 2.49 is in the Gray Area Zone, in 2021 the Z-Score value drops to be with a Z-Scroe value of 1.48 in the bankrupt zone. In 2022 the Z-value obtained a value of 1.80 indicating the condition of the company indicated bankruptcy. And at its peak in 2023, the Z-Score number dropped dramatically to 1.35 and of course the potential for the company to experience bankruptcy is very strong, so based on the Altman Z-Score calculation, PT BATA Tbk has indicated bankruptcy.Meanwhile, the results of the Zmijewski analysis calculation predict that the company will experience bankruptcy with a Zm value in 2019 of 1.39, in 2020 of 2.22, in 2021 of 2.02, in 2022 of 3.97 and in 2023 of 3.66. From the comparison of the results of the two methods, the similarity of the results obtained and this method can be considered by companies in making decisions.